The Correlation between Students’ Reading Comprehension and Their Paraphrasing Ability in Narrative Text - Ade Resky Swarini; Dwi Anggani Linggar Bharati; Djoko Sutopo (ELT Forum: Journal of English Language Teaching, 2019)
Paraphrasing activity allows the students to interpret what they have understood from the text in reading activity. This study investigates the correlation of the students’ reading comprehension and their paraphrasing ability in narrative text. There are two hypotheses in this research; null hypothesis (Ho) and the alternative hypothesis (Ha). The null hypothesis says “There is no correlation between students’ reading comprehension and their paraphrasing ability in narrative text”. Then, Ha says “There is a correlation between students’ reading comprehension and their paraphrasing ability in narrative text”. The population of this study is the eleventh graders of SMAN 1 Ambarawa in the academic year of 2016/2017. The students of XI MIPA 5 are taken as the samples. The design of this study is explanatory research design. The data are gained by administering two kinds of tests; reading comprehension and paraphrasing tests. Those tests are administered twice by using two different texts. There are three main processes in applying this method in the study; the use of the scatterplot, Pearson product moment coefficient, and correlation coefficient interpretation. Scatterplots displays that there is a positive linear relationship. Then, the data are calculated by using the Pearson product moment to know the degree of relationship among the variables. The results of the computation of correlation coefficient applied to the sample are 0.67 and 0.84. The consultation to the critical value of the r Product Moment with 95% confidence level and the number of the subjects 32 is 0.349. It means that the results obtained from the computation are higher than its critical value. Next, the results of the computation of correlation coefficient are consulted to the criteria of correlation coefficient interpretation. The interpretations of the relationship are substantial and high to very high. It can be concluded that there is a significant positive relationship between students’ reading comprehension ability in narrative text (X) and their paraphrasing ability in narrative text (Y) on the eleventh graders of SMA Negeri 1 Ambarawa in the academic year of 2016/2017.